Pengaruh Perbedaan Ketinggian Perangkap Kuning Terhadap Hasil Tangkapan Serangga Pada Pertanaman Cabai (Capsicum annum L.) - Rahmatullah, Rahmatullah; Soedijo, Samharinto; Marsuni, Yusriadi (JURNAL PROTEKSI TANAMAN TROPIKA, 2025)
There are many problems and negative impacts caused by insects on chili plants (Capsicum annum L.), so one alternative environmentally friendly control method is to use insect traps, one of the traps that can be used is the yellow trap. The aim of this research is to find out how effective yellow traps are against pests in red chili plantations. This method uses a completely randomized design (CRD) with one factor consisting of four treatments (T1 30 cm, T2 60 cm, T3 90 cm and T4 120 cm), which was repeated 6 times. The results of this study showed that all yellow trap treatments showed that the treatment in the first to sixth weeks had no real effect on trap setting and tended to decrease the number of catches. It was found that the percentage of insect intensity in the observations showed that the highest percentage figure for the T3 treatment was 3.81%, while the lowest percentage figure for the T1 treatment was 3.28%.